Penyuluhan tentang Literasi Teknologi bagi Guru dan Siswa SD di Kota Ternate, Maluku Utara - Nurprihatina Hasan; Farida Maricar (Insan Kreasi Media, 2023)
The objectives of this community service in the form of digital literacy counseling for elementary school students and teachers in Ternate City are to help (1) increase the competency knowledge of elementary school students and teachers regarding communication and information technology, (2) use the internet effectively for learning, and be wise and ethical use and utilize communication and information technology. This counseling was held at SD Negeri 63, Tobololo Village, Ternate City, North Maluku on Saturday, September 24 2022 from 10.00 to 12.00 WIT. Participants who took part in the community service activities were 35 (thirty-five) students consisting of 10 (ten) grade 5 students and 25 (twenty-five) grade 6 students, and 1 (one) teacher. The method used in this PKM is counseling with lectures and questions and answers. This counseling on digital literacy has raised awareness and added insight into how to use digital tools such as smart cell phones and their applications wisely and effectively. In order to optimize the use of digital technology to support the achievement of students' learning processes, use social media that applies the principles of politeness, and keep away from hoaxes, teachers wisely monitor the use of digital technology, especially smart cellphones by their students at school